Restorative Justice With Female Offenders: The Neglected Role of Gender in Restorative Conferencing. (January 2018) - Österman, Linnéa; Masson, Isla
This article presents findings from a new qualitative study into female offenders' experiences of restorative conferencing in England and Wales. It is argued that gendered factors of crime and victimization have a definite impact on the restorative conference process, particularly in the areas of complex and interacting needs, differently natured conference engagements, and risks around shame, mental health, and stereotypical ideals of female behavior. For women to reap the full benefits of restorative justice, it is argued that the particular needs and circumstances of female offenders must not only be acknowledged, but also incorporated into the field and mainstreamed into practice.